Composite phase change material with high enthalpy value and high structure stability as well as preparation method and application of composite phase change material
By using porous supercrosslinked polystyrene support materials and crosslinking agents in phase change materials to form a rich pore structure, the liquid phase leakage and structural stability of phase change materials are solved, and the composite of high enthalpy and high thermal stability is achieved Phase change materials have the application prospects of latent heat storage materials.
Patent Information
- Application Number
- CN202411291142.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
AI Technical Summary
Existing phase change materials are prone to liquid phase leakage during solid-liquid phase change, and it is difficult to maintain structural stability under external pressure, which affects its performance and reliability, and the enthalpy and thermal stability need to be improved.
Porous supercrosslinked polystyrene is used as the supporting material to form a rich pore structure through Fuker alkylation reaction, fill the organic solid-liquid phase change material in it, use strong capillary force to prevent liquid phase leakage, and form rigidity through crosslinking agent Structure improves the enthalpy and thermal stability of the material.
The preparation of a high-enthalpy high-structure stable composite phase change material was achieved, with a leakage rate of less than 4%, and the structure remained intact under high pressure, with an enthalpy value greater than 180J/g, which significantly improved the mechanical strength and thermal stability of the material.
Smart Images

Figure CN119144297A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy storage materials, relates to composite phase change heat storage material technology, and specifically relates to a high enthalpy value, high structural stability, shape stable composite phase change material, and a preparation method and application thereof. Background Art
[0002] The main disadvantage of renewable energy sources such as solar energy is their intermittent nature. When the sun is not shining, no energy is generated. Thermal energy storage technology can solve the problem of temporal and spatial mismatch between thermal energy supply and demand. Phase change materials are widely used in thermal energy storage systems to integrate and manage renewable energy.
[0003] As one of the key materials for medium and low temperature phase change heat storage, organic phase change materials have attracted much attention from researchers due to their stable chemical properties, high heat storage density, small volume change, non-toxic and non-corrosive properties. Organic phase change materials store and release thermal energy through solid-liquid phase transitions. Common examples include paraffins, alkanes, polyols, and fatty acids. However, organic phase change materials are prone to liquid phase leakage during the solid-liquid phase change process. Currently, the main methods to solve the leakage problem are encapsulation and shape stability. Phase change materials are usually also required to have certain compressive resistance in practical applications. This is because phase change materials undergo volume changes during the phase change process. When external pressure is applied, if the material cannot withstand the pressure and deforms or breaks, it will affect its performance and reliability.
[0004] Encapsulation is mainly used to prepare phase change microcapsules, but this core-shell structure has poor mechanical strength and is easily damaged by extrusion; shape-stable composite phase change materials are usually composed of phase change materials and porous materials. Porous materials can be divided into four categories: 1. Metal foams, including foam copper-based, foam aluminum-based and foam nickel-based, have high thermal conductivity and high porosity, but the large pore size makes the phase change material easy to leak and the cost of use is high; 2. Carbon-based three-dimensional materials, including expanded graphite (EG), foamed graphite, foamed carbon and graphene aerogel, although these materials have low conductivity, Good thermal properties, high porosity, large specific surface area, but poor mechanical properties, less amount of phase change material loaded, i.e. low latent heat, and higher cost; 3. Porous ceramics, although their cost is low, their specific surface area is low, and the amount of adsorbed phase change material is small; 4. Porous polymers, which are mainly composed of light elements such as C, H, O, and N, have weight advantages. They not only have excellent thermal reliability, good chemical stability, high mechanical strength, and low cost, but also have good compatibility with organic phase change materials, low density, and can load more phase change materials per unit mass. For example, Liu et al. (Fabrication of highly efficient thermal energy storage composite from waste polystyrenes. Chemical Engineering Science, 2020, 216: 115477) used waste polystyrene (PS) as a supporting material to achieve the shape stability of the phase change material, and paraffin as an organic solid-liquid phase change material. The enthalpy value of the prepared composite phase change material was 120.71 J / g, and the maximum loading rate of paraffin was 68.7%, and the loading capacity needs to be improved; Seitz S et al. (Self-assembling weak polyelectrolytes for the layer-by-layer encapsulation of paraffin-type phase change material icosane. Solar Energy Materials and Solar Cells, 2019, 190: 57-64) Using weak polyelectrolytes poly(acrylic acid) and poly(allylamine) to coat eicosane layer by layer, the enthalpy value of the obtained material can reach 199.1 J / g. The initial decomposition temperature obtained by TG test is 172.60°C, which is only about 5°C higher than that of pure eicosane. The thermal stability needs to be improved, and the compressive resistance also needs to be enhanced. Summary of the invention
[0005] In order to solve the above-mentioned problems of the phase change materials in the prior art, the present invention provides a high enthalpy value, high structural stability, shape-stable composite phase change material, and its preparation method and application. Specifically, the present invention uses porous super-crosslinked polystyrene obtained by Friedel-Crafts alkylation reaction of polystyrene and a crosslinking agent as a supporting material, and the organic solid-liquid phase change material is distributed in the pore structure of the super-crosslinked polystyrene. The composite phase change material can improve the structural stability of the system and has high mechanical strength. The strong capillary force of the matrix material can reduce the leakage of the phase change material during the solid-liquid phase change process, and in this process, the content of the supporting material can be minimized, so that the proportion of the phase change material is larger, that is, the enthalpy value of the composite phase change material is higher, and it has application prospects as a latent heat storage material.
[0006] Specifically, the present invention is implemented by the following technical solutions:
[0007] First, the present invention provides a high enthalpy, high structural stability, shape-stable composite phase change material, including an organic solid-liquid phase change material and a hyper-crosslinked polystyrene porous polymer, wherein the hyper-crosslinked polystyrene porous polymer includes polystyrene and a cross-linking agent for forming a cross-linked structure, and the hyper-crosslinked polystyrene porous polymer has a rich pore structure, and the organic solid-liquid phase change material is filled in the pores of the hyper-crosslinked polystyrene porous polymer, and the mass ratio of the organic solid-liquid phase change material, the polystyrene and the cross-linking agent is 10:(0.1-2.5):(0.5-3).
[0008] The present invention efficiently composites a porous polymer network support material with an organic solid-liquid phase change material, fills the phase change material in the pores of the network support structure, and uses strong capillary forces to prevent liquid phase leakage of the organic phase change material during the solid-liquid phase change process, thereby improving the structural stability of the composite phase change material. In addition, the organic solid-liquid phase change material and polystyrene have good compatibility, and the phase change material can be encapsulated while forming a super-crosslinked polystyrene structure, thereby ensuring a high enthalpy value of the composite phase change material, thereby obtaining a high-performance composite phase change material.
[0009] Preferably, the organic solid-liquid phase change material is one or more of organic alkanes and organic alcohols, including but not limited to one or more of C16-C24 straight-chain alkanes, paraffin, and polyvinyl alcohol, specifically n-octadecane, n-eicosane, etc., or paraffin, polyvinyl alcohol, etc.
[0010] Preferably, the average relative molecular weight (Mw) of the polystyrene is 10000-400000, more preferably 100000-400000. The larger the molecular weight of the polystyrene, the richer the pores of the formed hyper-crosslinked polystyrene porous polymer, which is more conducive to phase change material filling.
[0011] Preferably, the cross-linking agent includes one or more of dimethoxymethane, monochlorodimethyl ether, and 1,4-bis(chloromethyl)diphenyl.
[0012] Preferably, the leakage rate of the composite phase change material is lower than 4%, and the leakage rate of the molded sheet at 40Mpa is lower than 0.5% (4% is the leakage rate index after the sample itself is placed in a 60°C oven for 30 minutes, and 0.5% is the leakage rate index after the sample is molded into a sheet at 40Mpa and then placed in a 60°C oven for 3 hours). The initial decomposition temperature of TG is increased by 35°C relative to the pure phase change material, and the latent heat of phase change (melting enthalpy) is greater than 180J / g. In the present invention, the crosslinking agent and the benzene ring undergo FC alkylation reaction, and the covalent bridge formed by the crosslinking agent during the reaction makes the hyper-crosslinked network a rigid structure, which can prevent the spatial collapse between molecular chains caused by atomic accumulation, and make the polymer chain into permanent pores.
[0013] Secondly, the preparation method of the high enthalpy and high structural stability composite phase change material described in the present invention is to mix and dissolve the organic solid-liquid phase change material and polystyrene in an organic solvent, add a Lewis acid catalyst and a cross-linking agent, stir and react at 50-100°C for 12-24 hours to obtain a heterogeneous mixture, and then wash, filter and dry to obtain the composite phase change material.
[0014] In the above-mentioned preparation method, preferably, the mass ratio of the organic solid-liquid phase change material, polystyrene and cross-linking agent is 10:(0.1-2.5):(0.5-3), preferably 10:(0.1-1):(0.5-3), more preferably 10:(0.1-1):(1-3), and even more preferably 10:(0.1-0.5):(1-2).
[0015] In the above-mentioned preparation method, preferably, the organic solvent is one or more of 1,2-dichloroethane, chloroform, dichloromethane and carbon tetrachloride.
[0016] In the above-mentioned preparation method, preferably, the Lewis acid catalyst is one or both of ferric chloride and aluminum chloride.
[0017] As a preferred preparation method, it may include the following steps:
[0018] (1) melting the organic solid-liquid phase change material on a hot stage to obtain a liquid phase change material;
[0019] (2) mixing the liquid phase change material of step (1), the polystyrene and an organic solvent, stirring at 50-100° C. to fully dissolve the polystyrene, and the liquid phase change material, the polystyrene and the organic solvent are mixed to form a uniform and stable solution;
[0020] (3) adding a Lewis acid catalyst and a cross-linking agent to the mixed solution of step (2), stirring and reacting at 50-100° C. for 12-24 hours to obtain a heterogeneous mixture;
[0021] (4) Washing, filtering and drying the mixture of step (3) to obtain a composite phase change material.
[0022] Preferably, the solvent used for washing in step (4) is anhydrous methanol and hot water, and the number of washing times is 3-10 times.
[0023] The composite phase change material of the present invention uses porous super-crosslinked polystyrene obtained by Friedel-Crafts alkylation reaction of polystyrene and a crosslinking agent as a supporting material, and the organic solid-liquid phase change material is distributed in the pore structure of the super-crosslinked polystyrene. The composite phase change material can improve the structural stability of the system, and has high mechanical strength. The strong capillary force of the matrix material reduces the leakage of the phase change material during the solid-liquid phase change process, so that the leakage rate is lower than 4%, and in this process, the content of the supporting material is reduced as much as possible, so that the proportion of the phase change material is larger, that is, the enthalpy value of the composite phase change material is higher. In addition, the preparation process of the composite phase change material of the present invention is simple and the energy consumption is low. The high enthalpy value, high structural stability, shape-stable composite phase change material of the present invention is used as a latent heat storage material, the phase change latent heat is greater than 180J / g, and a pressure of 40Mpa is applied to it, the structure remains intact, and the leakage rate is lower than 0.5%, which has an application prospect as a latent heat storage material.
[0024] Thirdly, the high enthalpy, high structural stability, shape-stable composite phase change material described in the present invention can be used as a latent heat energy storage material, and the phase change latent heat is greater than 180 J / g.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention provides a high enthalpy value, high structural stability, shape-stable composite phase change material, which can improve the structural stability of the system, prevent liquid phase leakage, and has high mechanical strength. The strong capillary force of the matrix material can be used to reduce the leakage of the phase change material during the solid-liquid phase change process, so that the leakage rate is less than 4%. In this process, the content of the supporting material is minimized to make the proportion of the phase change material larger, that is, the enthalpy value of the composite phase change material is higher.
[0027] (2) The present invention also provides a method for preparing a high enthalpy value, high structural stability, shape-stable composite phase change material, which has a simple preparation process and low energy consumption.
[0028] (3) The high enthalpy, high structural stability, shape-stable composite phase change material of the present invention is used as a latent heat storage material, the phase change latent heat is greater than 180 J / g, and a pressure of 40 MPa is applied to it, the structure remains intact, and the leakage rate is less than 0.5%, which has application prospects as a latent heat storage material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the formation mechanism of the hyper-crosslinked polystyrene of the present invention.
[0030] Figure 2 The figure is a schematic diagram of the preparation process of the composite phase change material for energy storage of the present invention.
[0031] Figure 3 This is a DSC test chart of the hyper-crosslinked polystyrene / eicosane (polystyrene PS: dimethoxymethane FDA = 3:0) composite phase change material prepared in Example 1 of the present invention.
[0032] Figure 4 This is a DSC test chart of the hyper-crosslinked polystyrene / eicosane (PS:FDA=5:1) composite phase change material prepared in Example 2 of the present invention.
[0033] Figure 5 This is a DSC test chart of the hyper-crosslinked polystyrene / eicosane (PS:FDA=1:5) composite phase change material prepared in Example 3 of the present invention.
[0034] Figure 6 This is a DSC test chart of the hyper-crosslinked polystyrene / eicosane (PS:FDA=1:12) composite phase change material prepared in Example 4 of the present invention.
[0035] Figure 7 This is a DSC test chart of the hyper-crosslinked polystyrene / eicosane (PS:FDA=1:15) composite phase change material prepared in Example 5 of the present invention.
[0036] Figure 8 TG test graphs of Examples 3, 4, 5 and eicosane of the present invention.
[0037] Fig. 9 This is a scanning electron microscope image of the hyper-crosslinked polystyrene / eicosane (PS:FDA=1:12) composite phase change material prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0038] The technical solution of the present invention will be further described in detail below in conjunction with the embodiments: Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0040] Example 1
[0041] (1) Melt solid eicosane on a hot plate to obtain liquid eicosane (C 20 );
[0042] (2) Mix 10 g of the liquid eicosane prepared in step (1), 3 g of polystyrene (PS, Sigma-Aldrich, Mw ≈ 192,000) and 35 ml of 1,2-dichloroethane (DCE) at 80° C. to fully dissolve PS. Stir until C 20 , PS and DCE are homogenized to form a uniform and stable solution;
[0043] (3) adding 0.5 g of anhydrous ferric chloride (FeCl3) and 0 g of dimethoxymethane (FDA) to the mixed solution of step (2), and continuing to stir and react at 80°C for 20 hours to obtain a heterogeneous mixture, wherein the mass ratio PS:FDA=3:0;
[0044] (4) The mixture of step (3) was washed three times with anhydrous methanol and 60° C. hot water respectively, filtered and dried to obtain a composite phase change material.
[0045] The loading rate of eicosane in the obtained composite phase change material (E en ) is 83.13%, the melting enthalpy is 208.9 J / g, and the leakage rate is 9.50% after being directly placed in a 60°C oven for 30 minutes.
[0046] Load rate (E en ) is calculated as follows:
[0047]
[0048] in, is the melting enthalpy of the composite phase change material, ΔH m,Pure PCM is the melting enthalpy of the pure phase change material
[0049] The pure C was tested by differential scanning calorimetry (DSC) (Q2000, New Castle, DE, USA). 20 and HCPS-C 20Melting enthalpy of composite phase change material. In pure nitrogen atmosphere, the heating rate was 10℃ / min, the test temperature range was 0-60℃, and about 5mg of sample was used in DSC analysis. The melting enthalpy of the sample was calculated by NETZSCH Proteus Thermal Analysis.
[0050] Leakage rate (L r ) to evaluate HCPS-C 20 Leakage resistance of composite phase change materials. All samples were placed in an oven at 60°C to test the leakage rate. The initial mass of the sample was marked as M0, and the mass of the sample was weighed regularly and recorded as M. t . Calculate the leakage rate (L r ):
[0051]
[0052] Example 2
[0053] (1) Melt solid eicosane on a hot plate to obtain liquid eicosane (C 20 );
[0054] (2) Mix 10 g of the liquid eicosane prepared in step (1), 2.5 g of polystyrene (PS, Mw ≈ 192,000) and 35 ml of 1,2-dichloroethane (DCE) at 80° C. to fully dissolve PS. Stir until C 20 , PS and DCE are homogenized to form a uniform and stable solution;
[0055] (3) adding 0.5 g of anhydrous ferric chloride (FeCl3) and 0.5 g of dimethoxymethane (FDA) to the mixed solution of step (2), and continuing to stir and react at 80°C for 20 hours to obtain a heterogeneous mixture, wherein the mass ratio PS:FDA=5:1;
[0056] (4) The mixture of step (3) was washed three times with anhydrous methanol and 60° C. hot water respectively, filtered and dried to obtain a composite phase change material.
[0057] The loading rate of eicosane in the obtained composite phase change material is 13.43%, the melting enthalpy is 33.74 J / g, the initial decomposition temperature of TG is 185.06°C, and the leakage rate is 2.99% after being directly placed in a 60°C oven for 30 minutes. After being molded into a sheet at 40 MPa, a circular sample is obtained, and the leakage rate is 0.36% after being placed in a 60°C oven for 3 hours. In this example, although the melting enthalpy is not very high when a small amount of FDA is added, compared with Example 1 without adding the crosslinking agent FDA, this example can achieve the purpose of structural stability, and the leakage rate is less than 4%. The subsequent examples continue to add FDA to achieve the dual purpose of high melting enthalpy and stable structure.
[0058] Example 3
[0059] (1) Melt solid eicosane on a hot plate to obtain liquid eicosane (C 20 );
[0060] (2) Mix 10 g of the liquid eicosane prepared in step (1), 0.5 g of polystyrene (PS, Mw ≈ 192,000) and 35 ml of 1,2-dichloroethane (DCE) at 80° C. to fully dissolve PS. Stir until C 20 , PS and DCE are homogenized to form a uniform and stable solution;
[0061] (3) adding 0.5 g of anhydrous ferric chloride (FeCl3) and 2.5 g of dimethoxymethane (FDA) to the mixed solution of step (2), and continuing to stir and react at 80°C for 20 hours to obtain a heterogeneous mixture, wherein the mass ratio PS:FDA=1:5;
[0062] (4) The mixture of step (3) was washed three times with anhydrous methanol and 60° C. hot water respectively, filtered and dried to obtain a composite phase change material.
[0063] The loading rate of eicosane in the obtained composite phase change material is 74.37%, the melting enthalpy is 186.9 J / g, the TG initial decomposition temperature is 193.57°C, and the leakage rate is 0.194% after being directly placed in a 60°C oven for 30 minutes. A circular sample is obtained after being molded into a sheet at 40 MPa. After being placed in a 60°C oven for 3 hours, the leakage rate is 0.13%.
[0064] Example 4
[0065] (1) Melt solid eicosane on a hot plate to obtain liquid eicosane (C 20 );
[0066] (2) Mix 10 g of the liquid eicosane prepared in step (1), 0.231 g of polystyrene (PS, Mw ≈ 192,000) and 35 ml of 1,2-dichloroethane (DCE) at 80° C. to fully dissolve PS. Stir until C 20 , PS and DCE are homogenized to form a uniform and stable solution;
[0067] (3) adding 0.5 g of anhydrous ferric chloride (FeCl3) and 2.769 g of dimethoxymethane (FDA) to the mixed solution of step (2), and continuing to stir and react at 80°C for 20 hours to obtain a heterogeneous mixture, wherein the mass ratio PS:FDA=1:12;
[0068] (4) The mixture of step (3) was washed three times with anhydrous methanol and 60° C. hot water respectively, filtered and dried to obtain a composite phase change material.
[0069] The loading rate of eicosane in the obtained composite phase change material is 79.83%, the melting enthalpy is 200.6 J / g, the TG initial decomposition temperature is 188.78°C, and the leakage rate is 0.097% after being directly placed in a 60°C oven for 30 minutes. A circular sample is obtained after being molded into a sheet at 40 MPa. After being placed in a 60°C oven for 3 hours, the leakage rate is 0.29%.
[0070] Example 5
[0071] (1) Melt solid eicosane on a hot plate to obtain liquid eicosane (C 20 );
[0072] (2) Mix 10 g of the liquid eicosane prepared in step (1), 0.188 g of polystyrene (PS, Mw ≈ 192,000) and 35 ml of 1,2-dichloroethane (DCE) at 80° C. to fully dissolve PS. Stir until C 20 , PS and DCE are homogenized to form a uniform and stable solution;
[0073] (3) adding 0.5 g of anhydrous ferric chloride (FeCl3) and 2.812 g of dimethoxymethane (FDA) to the mixed solution of step (2), and continuing to stir and react at 80°C for 20 hours to obtain a heterogeneous mixture, wherein the mass ratio PS:FDA=1:15;
[0074] (4) The mixture of step (3) was washed three times with anhydrous methanol and 60° C. hot water respectively, filtered and dried to obtain a composite phase change material.
[0075] The loading rate of eicosane in the obtained composite phase change material is 71.91%, the melting enthalpy is 180.7 J / g, the TG initial decomposition temperature is 191.25°C, and the leakage rate is 0.478% after it is directly placed in a 60°C oven for 30 minutes. A circular sample is obtained after being molded into a sheet at 40 MPa. After being placed in a 60°C oven for 3 hours, the leakage rate is 0.47%.
[0076] The leakage rate of the composite phase change material is lower than 4%, and the initial decomposition temperature of TG is increased by 10-35° C. compared with the organic solid-liquid phase change material.
[0077] Example 1 does not introduce the cross-linking agent dimethoxymethane FDA, while Examples 2-5 introduce the cross-linking agent FDA. The introduction of FDA increases the structural stability of the composite phase change material and reduces the leakage rate of the composite phase change material. After the introduction of FDA, polystyrene will cross-link with FDA to form hyper-cross-linked polystyrene. Hyper-cross-linked polystyrene has low skeleton density, high specific surface area, good physical and chemical stability, a greater degree of cross-linking, and a high degree of rigidity in the polymer network, which prevents the tight contraction of the polymer chain, and a stable pore structure. The composite phase change material formed after the adsorption of the phase change material is more stable in structure and has a lower leakage rate. The preparation of a high enthalpy value and a high structural stability composite phase change material can be achieved by adjusting polystyrene PS / dimethoxymethane FDA.
[0078] Example 6
[0079] (The organic solid-liquid phase change material is paraffin)
[0080] (1) Melting solid paraffin on a hot plate to obtain liquid paraffin (PW);
[0081] (2) at 80° C., 10 g of the liquid paraffin prepared in step (1), 0.231 g of polystyrene (PS, Mw-192000) and 35 ml of 1,2-dichloroethane (DCE) were mixed to fully dissolve the PS, and the PW, PS and DCE were homogenized by stirring to form a uniform and stable solution;
[0082] (3) adding 0.5 g of anhydrous ferric chloride (FeCl3) and 2.769 g of dimethoxymethane (FDA) to the mixed solution of step (2), and continuing to stir and react at 80°C for 20 hours to obtain a heterogeneous mixture, wherein the mass ratio PS:FDA=1:12;
[0083] (4) The mixture of step (3) was washed three times with anhydrous methanol and 60° C. hot water respectively, filtered and dried to obtain a composite phase change material.
[0084] The paraffin loading rate in the obtained composite phase change material is 78.64%, the melting enthalpy is 181.5 J / g, the TG initial decomposition temperature is 266.34°C, and the leakage rate is 0.684% after being directly placed in a 60°C oven for 30 minutes. A circular sample is obtained after being molded into a sheet at 40 MPa. After being placed in a 60°C oven for 3 hours, the leakage rate is 0.25%.
[0085] Example 7
[0086] (The cross-linking agent is monochlorodimethyl ether MCDE)
[0087] (1) Melt solid eicosane on a hot plate to obtain liquid eicosane (C 20 );
[0088] (2) Mix 10 g of the liquid eicosane prepared in step (1), 0.231 g of polystyrene (PS, Mw ≈ 192,000) and 35 ml of 1,2-dichloroethane (DCE) at 80° C. to fully dissolve PS. Stir until C 20 , PS and DCE are homogenized to form a uniform and stable solution;
[0089] (3) adding 0.5 g of anhydrous ferric chloride (FeCl3) and 2.769 g of monochlorodimethyl ether (MCDE) to the mixed solution of step (2), and continuing to stir and react at 80°C for 20 hours to obtain a heterogeneous mixture, wherein the mass ratio PS:MCDE=1:12;
[0090] (4) The mixture of step (3) was washed three times with anhydrous methanol and 60° C. hot water respectively, filtered and dried to obtain a composite phase change material.
[0091] The loading rate of eicosane in the obtained composite phase change material is 78.42%, the melting enthalpy is 197.07 J / g, the TG initial decomposition temperature is 190.69°C, and the leakage rate is 0.546% after being directly placed in a 60°C oven for 30 minutes. A circular sample is obtained after being molded into a sheet at 40 MPa. After being placed in a 60°C oven for 3 hours, the leakage rate is 0.34%.
[0092] Example 8
[0093] (The cross-linking agent is 1,4-bis(chloromethyl)diphenyl CMDP)
[0094] (1) Melt solid eicosane on a hot plate to obtain liquid eicosane (C 20 );
[0095] (2) Mix 10 g of the liquid eicosane prepared in step (1), 0.231 g of polystyrene (PS, Mw ≈ 192,000) and 35 ml of 1,2-dichloroethane (DCE) at 80° C. to fully dissolve PS. Stir until C 20 , PS and DCE are homogenized to form a uniform and stable solution;
[0096] (3) adding 0.5 g of anhydrous ferric chloride (FeCl3) and 2.769 g of 1,4-bis(chloromethyl)diphenylamine (CMDP) to the mixed solution of step (2), and continuing to stir and react at 80°C for 20 hours to obtain a heterogeneous mixture, wherein the mass ratio of PS:CMDP is 1:12;
[0097] (4) The mixture of step (3) was washed three times with anhydrous methanol and 60° C. hot water respectively, filtered and dried to obtain a composite phase change material.
[0098] The loading rate of eicosane in the obtained composite phase change material is 79.02%, the melting enthalpy is 198.58 J / g, the TG initial decomposition temperature is 190.32°C, and the leakage rate is 0.463% after being directly placed in a 60°C oven for 30 minutes. A circular sample is obtained after being molded into a sheet at 40 MPa. After being placed in a 60°C oven for 3 hours, the leakage rate is 0.42%.
[0099] It should be noted that the above-mentioned technical contents of the present invention are only for explanation and clarification to enable those skilled in the art to understand the technical essence of the present invention, so the technical contents are not used to limit the substantial protection scope of the present invention. The substantial protection scope of the present invention shall be subject to the claims. Those skilled in the art should know that any modification, equivalent substitution and improvement based on the substantial spirit of the present invention shall be within the substantial protection scope of the present invention.
Claims
1. A high enthalpy and high structural stability composite phase change material, characterized in that: It includes an organic solid-liquid phase change material and a hyper-crosslinked polystyrene porous polymer. The hyper-crosslinked polystyrene porous polymer includes polystyrene and a crosslinking agent. The hyper-crosslinked polystyrene porous polymer has a rich pore structure. The organic solid-liquid phase change material is filled in the pores of the hyper-crosslinked polystyrene porous polymer.
2. The high enthalpy and high structural stability composite phase change material according to claim 1, characterized in that: The organic solid-liquid phase change material is one or more of organic alkanes and organic alcohols.
3. The high enthalpy and high structural stability composite phase change material according to claim 1, characterized in that: The average relative molecular weight of the polystyrene is 10,000-400,000.
4. The high enthalpy and high structural stability composite phase change material according to claim 1, characterized in that: The cross-linking agent includes one or more of dimethoxymethane, monochlorodimethyl ether, and 1,4-bis(chloromethyl)diphenyl.
5. A method for preparing a high enthalpy and highly structurally stable composite phase change material according to any one of claims 1 to 4, comprising mixing and dissolving an organic solid-liquid phase change material and polystyrene in an organic solvent, adding a Lewis acid catalyst and a cross-linking agent, stirring and reacting at 50-100° C. for 12-24 hours to obtain a heterogeneous mixture, and then washing, filtering, and drying to obtain a composite phase change material.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the organic solid-liquid phase change material, polystyrene and cross-linking agent is 10:(0.1-2.5):(0.5-3).
7. The preparation method according to claim 5, characterized in that: The organic solvent is one or more of 1,2-dichloroethane, chloroform, dichloromethane and carbon tetrachloride.
8. The preparation method according to claim 5, characterized in that: The Lewis acid catalyst is one or both of ferric chloride and aluminum chloride.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The following steps are involved: (1) melting the organic solid-liquid phase change material on a hot stage to obtain a liquid phase change material; (2) mixing the liquid phase change material, polystyrene and organic solvent of step (1), stirring at 50-100° C. to fully dissolve the polystyrene, and the liquid phase change material, the polystyrene and the organic solvent are mixed to form a uniform and stable solution; (3) adding a Lewis acid catalyst and a cross-linking agent to the mixed solution of step (2), stirring and reacting at 50-100° C. for 12-24 hours to obtain a heterogeneous mixture; (4) Washing, filtering and drying the mixture of step (3) to obtain a composite phase change material.
10. Use of the high enthalpy and high structural stability composite phase change material according to any one of claims 1 to 4 or obtained by the preparation method according to any one of claims 5 to 9, characterized in that: Used as latent heat storage material, the phase change latent heat is greater than 180J / g.
Citation Information
Patent Citations
Preparation method of super-crosslinked polystyrene-supported organic phase change material and composite phase change material prepared by preparation method
CN109836598A
Composite phase-change material taking polystyrene with siloxy functional group as supporting material as well as preparation method and application of composite phase-change material
CN112143462A
Beeswax / polystyrene composite phase-change energy storage material and preparation method and application thereof
CN112266770A
PW (at) PS / BNNSs phase change microcapsule with excellent heat conduction and heat storage performance and preparation method of PW (at) PS / BNNSs phase change microcapsule
CN115491181A
